Prevention of complications and risk reduction in oral implantology considering human factors and situation awareness - González-Silva, Nadia Yudy (2021)
In recent years, the percentage of dental implant placement has increased, and the presence of adverse events and complications are not uncommon. The vast majority of recommendations for reducing complications associated with dental implant placement are analyzed from the point of view of their direct causes, evaluating the technique and/or the individual, but not the system as a whole, being this the actual etiology of complications. The inclusion of human factors and situation awareness has recently gained increasing importance in oral implantology complications and has allowed global analysis of both the individual and the environment, providing solutions based on prevention. However, knowledge and use of these aspects in oral implantology are still in the process of popularization, and therefore, the objective of this article was to describe the human factors involved and situation awareness for preventing complications and reducing the risks associated with dental implant placement procedures.